Mystery Science Theater 3000 [videorecording (DVD)] : the movie - Mallon, Jim director; Nelson, Michael J.; Beaulieu, Trace, 1958- (Universal Studios Home Entertainment, 2008)
The mad and evil scientist, Dr. Clayton Forrester, has created a scheme that he hopes will gain him world domination. He plans to torment Mike Nelson and the robots by sending them the worst ever B-movie to watch called, "This Island Earth." He is convinced that this movie will drive them insane. The guys cannot control when the movie begins or ends, and they are forced to witness this truely horrorible movie - including a lobster creature dressed in slacks. Now it will have to be up to one test subject's quick wit, sharp sense of humor, and utter intolerance for cinematic garbage, to foil the plans of the scientist and to save the Earth.